Mengenali Nyeri Pinggang dan Faktor-Faktor yang Mempengaruhi Remaja dan Lansia - Riani Baiduri Siregar; Heri Saputra; Rudi Purwana (Lembaga Pengembangan Kinerja Dosen, 2025)
Low back pain (LBP) is a common health issue that affects both adolescents and the elderly, impacting their daily activities and overall quality of life. This study aims to identify the causes, risk factors, and preventive measures associated with LBP in these two age groups. Various factors, including posture, physical activity, body weight, and occupational or academic demands, contribute to the prevalence of LBP. In adolescents, prolonged sitting, improper posture, and excessive screen time are significant contributors, while in the elderly, age-related degenerative changes, decreased muscle strength, and chronic conditions such as osteoporosis play a major role. This study utilizes a literature review and observational analysis to explore the similarities and differences in LBP risk factors across different age groups. The findings suggest that early prevention through proper ergonomics, regular exercise, and healthy lifestyle choices can help reduce the incidence of LBP. Additionally, awareness and education about spinal health should be emphasized in both adolescents and the elderly to mitigate future complications. This research highlights the importance of a multidisciplinary approach, including physiotherapy, medical interventions, and lifestyle modifications, in managing and preventing LBP effectively.